1995
DOI: 10.1111/j.1399-302x.1995.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of biotypes and antimicrobial susceptibility of Actinobacillus actinomycetemcomitans

Abstract: Eighty isolates of Actinobacillus actinomycetemcomitans from 30 Brazilian periodontitis patients were examined to determine the distribution of biotypes and in vitro antimicrobial susceptibility. Seventy-seven percent of the isolates belonged to biotype X. All A. actinomycetemcomitans isolates were susceptible to cefoxitin, imipenem and tetracycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
3
7
0
7
Order By: Relevance
“…In this study, by culture, A. actinomycetemcomitans was isolated from 18% of the periodontal patients and 2% of the healthy subjects, in accordance with Asikainen et al (1) and Malheiros and AvilaCampos (22). Moreover, studies have shown that the occurrence of A. actinomycetemcomitans varied from 20% to 80% in adult periodontitis patients (3,22,33). On the other hand, by using a PCR method, this microorganism was detected in 44% of the periodontal patients, and in 16% of the healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, by culture, A. actinomycetemcomitans was isolated from 18% of the periodontal patients and 2% of the healthy subjects, in accordance with Asikainen et al (1) and Malheiros and AvilaCampos (22). Moreover, studies have shown that the occurrence of A. actinomycetemcomitans varied from 20% to 80% in adult periodontitis patients (3,22,33). On the other hand, by using a PCR method, this microorganism was detected in 44% of the periodontal patients, and in 16% of the healthy subjects.…”
Section: Discussionsupporting
confidence: 87%
“…In healthy subjects, biotypes II, VI and X were observed. Few studies have shown the presence of biotypes in A. actinomycetemcomitans and the biotype II appears to be the most prevalent in Brazilian periodontal patients (3,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,8 Para profundizar en el estudio de A. actinomycetemcomitans se puede biotipar haciendo pruebas de fermentación de carbohidratos, dextrina, maltosa, manitol y xilosa. 23,25 Las pruebas serológicas se realizan para identificar los 7 serotipos (A -G). 26,28 Pruebas moleculares como PCR convencional y en tiempo real, son usados por ser muy sensibles y específicos para el diagnóstico de microorganismos.…”
Section: Fisiopatologíaunclassified
“…6 Es de importancia mencionar la transmisión del A. actinomycetemcomitans de padres a hijos, ya que estudios de biotipos y serotipos bacterianos en los componentes de la familia, han demostrado un contagio de tipo intrafamiliar. 25,28,31 Tratamiento mecánico y antimicrobiano para A. actinomycetemcomitans El tratamiento mecánico se basa en la fase I de la terapia periodontal, la cual consiste en la eliminación de placa y tártaro supra y subgingival, así como un alisado de la superficie radicular, para evitar superficies rugosas que permitan mayor retención de placa. Instruir al paciente en el control de placa por debajo del 20 % del índi-ce de higiene según O'leary y de una reevaluación periódica de su caso.…”
Section: A Actinomycetemcomitans Pertenece Al Grupo Hacek (H Aphropunclassified